Detection of early radiotherapy‐induced changes in intrinsic myocardial contractility by ultrasound tissue characterization in patients with early‐stage breast cancer. Issue 2 (February 2017) - Tuohinen, Suvi Sirkku; Skyttä, Tanja; Huhtala, Heini; Virtanen, Vesa; Virtanen, Marko; Kellokumpu‐Lehtinen, Pirkko‐Liisa; Raatikainen, Pekka
Abstract : Background: Increased cardiovascular morbidity and mortality are major late complications after radiotherapy (RT) in the thoracic region. Ultrasound tissue characterization (UTC) is a noninvasive method for the identification of myocardial changes. The aim of this prospective clinical trial was to assess whether the analysis of cyclic variation of integrated backscatter (CVIBS) can detect early RT‐induced myocardial alterations. Methods: Seventy‐three eligible patients with early‐stage breast cancer were evaluated before and immediately after adjuvant RT. Twenty and 53 patients had right‐sided and left‐sided breast cancer, respectively. None of the patients received chemotherapy. Comprehensive echocardiographic examination included three‐dimensional (3D) measurements and UTC analysis of the left ventricular (LV) septum and posterior wall. Results: RT reduced CVIBS in a dose‐dependent manner. The mean heart radiation dose over two gray (Gy) reduced the septal CVIBS from 12.0±3.4 to 9.6±2.5 dB ( P <.001) and the posterior wall CVIBS from 12.8±2.7 to 11.3±2.4 dB ( P =.007). The CVIBS remained unchanged when the mean heart RT dose was below 2 Gy. Multivariate analysis showed an independent association with a change in septal CVIBS and the use of aromatase inhibitor (β=2.986, P =.001) and body mass index (β=−0.241, P =.014). The posterior values were worse with higher mean lung dose (β=‐.485, P =.018) and with nonsmoking status (β=−2.411, P =.009). Echocardiography parameters showed increased myocardial mass but conventional measurements of the LV systolic function remained unchanged. Conclusions: Cyclic variation of integrated backscatter analysis seems to be a sensitive method to detect early RT‐induced myocardial changes. Hence, it may be useful in screening of patients needing closer follow‐up.